MENINGKATKAN PERAN SERTA MASYARAKAT DALAM UPAYA MENUJU DESA MANDIRI DAN TANGGUH DITENGAH WABAH - Subayani, Nataria Wahyuning; Alfajar, Yulfanani; Rahaweni, Mirna Hanes; Suharyani, Dwi Retno; Hibatullah, Mohammad Rizqi (Universitas Muhammadiyah Gresik, 2022)
In the midst of the COVID-19 pandemic, many residents have been affected both economically, in terms of education and health. The need for counseling or education to the surrounding community on the importance of taking care of yourself, especially protecting yourself from the Covid-19 virus. With several work programs carried out by the group 1 KKN team in their respective villages, it is hoped that they can help the government in suppressing the spread of the COVID-19 virus. Besides protecting ourselves is the first step to take care of the people around us. When people ignore the importance of taking care of themselves, especially ignoring health protocols, it also affects those around us. After the work program is carried out by members of group 1 KKN, it is hoped that the community will be able to protect themselves and always comply with the health protocols that have been set to maintain mutual safety